Identification of Immunoglobulin G Autoantibody Against Malondialdehyde-Acetaldehyde Adducts as a Novel Serological Biomarker for Ulcerative Colitis. Issue 4 (14th April 2022) - Duryee, Michael J.; Ahmad, Rizwan; Eichele, Derrick D.; Hunter, Carlos D.; Mitra, Ananya; Talmon, Geoffrey A.; Singh, Shailender; Smith, Lynette M.; Rosen, Michael J.; Dhawan, Punita; Thiele, Geoffrey M.; Singh, Amar B.
Abstract : INTRODUCTION: Inflammatory bowel disease (IBD) is associated with immune responses with oxidative stress wherein high levels of malondialdehyde result in the formation of a highly stable and immunogenic malondialdehyde-acetaldehyde adduct (MAA). Thus, this study evaluated the status of MAA and anti-MAA antibody isotypes in IBD and their potential as novel serological biomarkers for differentiating ulcerative colitis (UC) from Crohn's disease (CD). METHODS: Levels of MAA and anti-MAA antibodies were examined in patients with IBD (171), non-IBD gastrointestinal diseases (77), and controls (83) from 2 independent cohorts using immunohistochemistry and enzyme-linked immunosorbent assay. Receiver operating characteristic curves and Youden cutoff index from logistic regression were used to determine the sensitivity and specificity. RESULTS: The MAA and blood immunoglobulin G (IgG) anti-MAA antibody levels were significantly elevated in IBD compared with non-IBD patients ( P = 0.0008) or controls ( P = 0.02). Interestingly, patients with UC showed higher levels of IgG anti-MAA ( P < 0.0001) than patients with CD including those with colonic CD ( P = 0.0067). The odds ratio by logistic regression analysis predicted stronger association of IgG anti-MAA antibody with UC than CD. Subsequent analysis showed that IgG anti-MAA antibody levels could accurately identify ( P = 0.0004) UC in the adult cohort with a sensitivity of 75.3% and a specificity of 71.4% and an area under the curve of 0.8072 (0.7121–0.9024). The pediatric cohort also showed an area under the curve of 0.8801 (0.7988–0.9614) and precisely distinguished ( P < 0.0001) UC with sensitivity (95.8%) and specificity (72.3%). DISCUSSION: Circulating IgG anti-MAA antibody levels can serve as a novel, noninvasive, and highly sensitive test to identify patients with UC and possibly differentiate them from patients with CD.